2018
DOI: 10.2147/jpr.s182227
|View full text |Cite
|
Sign up to set email alerts
|

Influence of needle-insertion depth on epidural spread and clinical outcomes in caudal epidural injections: a randomized clinical trial

Abstract: BackgroundA caudal epidural steroid injection (CESI) is a commonly used method to improve symptoms of lumbosacral pain. We compared the achievement of successful epidurograms and patient-reported clinical outcomes following different needle-insertion depths during CESI.MethodsFor the conventional method group, the needle was advanced into the sacral canal. For the alternative method group, the needle was positioned immediately after penetration of the sacrococcygeal ligament. Epidural filling patterns and vasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Third, the epidural venous plexus is gathered at the anterior part of the sacral canal and ends at the S4 level or lower [ 17 ]. In the conventional technique, the needle comes into contact with the anterior wall of the sacral spine because of the kyphotic nature of the sacrum [ 10 , 11 ]. Doo et al [ 11 ] reported that intravascular injection incidences during a US-guided conventional technique with a disposable nerve blockade needle (25-gauge, 5 cm short-bevel needle) was 24.0% (6 of 25), as confirmed by fluoroscopy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Third, the epidural venous plexus is gathered at the anterior part of the sacral canal and ends at the S4 level or lower [ 17 ]. In the conventional technique, the needle comes into contact with the anterior wall of the sacral spine because of the kyphotic nature of the sacrum [ 10 , 11 ]. Doo et al [ 11 ] reported that intravascular injection incidences during a US-guided conventional technique with a disposable nerve blockade needle (25-gauge, 5 cm short-bevel needle) was 24.0% (6 of 25), as confirmed by fluoroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Doo et al [ 11 ] reported that intravascular injection incidences during a US-guided conventional technique with a disposable nerve blockade needle (25-gauge, 5 cm short-bevel needle) was 24.0% (6 of 25), as confirmed by fluoroscopy. Park et al [ 10 ] reported that intravascular injection occurrences were 20.3% (13 of 64) during a fluoroscopically guided conventional technique using a spinal needle (22-gauge, 8 cm Quincke) advanced to the mid-S3 level. They mention that unintentional intravascular injection might be caused by needle trauma in the vessel-rich zone in the sacral canal and direct needle contact to the sacral bone during the execution of the conventional technique.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple prior publications regarding contrast injection prior to medication injection demonstrated rates of vascular uptake of contrast at various injection sites. Examples include vascular uptake rates of 20% for caudal epidural steroid injections[ 4 ] and 17%, 6%, 8%, and 21%, for sacral, lumbar, thoracic, and cervical transforaminal epidural injections, respectively. [ 5 ]…”
Section: Introductionmentioning
confidence: 99%